Enhanced Surfactant Protein and Defensin mRNA Levels and Reduced Viral Replication during Parainfluenza Virus Type 3 Pneumonia in Neonatal Lambs - Grubor, Branka (American Society for Microbiology, 2004)
Defensins and surfactant protein A (SP-A) and SP-D are antimicrobial components of the pulmonary innate immune system. The purpose of this study was to determine the extent to which parainfluenza type 3 virus infection in neonatal lambs alters expression of sheep beta-defensin 1 (SBD-1), SP-A, and SP-D, all of which are constitutively transcribed by respiratory epithelia. Parainfluenza type 3 viral antigen was detected by immunohistochemistry (IHC) in the bronchioles of all infected lambs 3 days postinoculation and at diminished levels 6 days postinoculation, but it was absent 17 days postinoculation. At all times postinoculation, lung homogenates from parainfluenza type 3 virus-inoculated animals had increased SBD-1, SP-A, and SP-D mRNA levels as detected by fluorogenic real-time reverse transcriptase PCR. Protein levels of SP-A in lung homogenates detected by quantitative-competitive enzyme-linked immunosorbent assay and protein antigen of SP-A detected by IHC were not altered. These studies demonstrate that parainfluenza type 3 virus infection results in enhanced expression of constitutively transcribed innate immune factors expressed by respiratory epithelia and that this increased expression occurs concurrently with decreased viral replication.